2011
DOI: 10.1088/0953-8984/23/17/176003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic behavior of a mixed Ising 3/2 and 5/2 spin model

Abstract: We perform Monte Carlo simulations in order to study the magnetic properties of the mixed spin-S = ± 3/2, ± 1/2 and spin-σ = ± 5/2, ± 3/2, ± 1/2 Ising model. The spins are alternated on a square lattice such that S and σ are nearest neighbors. We found that when the Hamiltonian includes antiferromagnetic interactions between the S and σ spins, ferromagnetic interactions between the spins S, and a crystal field, the system presents compensation temperatures in a certain range of the parameters. The compensation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 49 publications
(54 reference statements)
1
12
0
6
Order By: Relevance
“…Around the multiphase points may emerge abundant critical phenomena, such as first order phase transitions and tricritical points [10,11]. Furthermore, the exact calculation of the ground state energies can check the reliability of the results of the numerical simulation, as shown by Monte Carlo studies of Wei et al on critical phenomena in a spin (1, 3/2) Ising model in a cubic lattice [11] and De La Espriella and Buendía, on the magnetic behavior of a spins (3/2, 5/2) model, where they found that the ground state magnetizations of the system match with those obtained at T ¼0 in phase diagrams at finite temperature [12].…”
Section: Introductionmentioning
confidence: 65%
“…Around the multiphase points may emerge abundant critical phenomena, such as first order phase transitions and tricritical points [10,11]. Furthermore, the exact calculation of the ground state energies can check the reliability of the results of the numerical simulation, as shown by Monte Carlo studies of Wei et al on critical phenomena in a spin (1, 3/2) Ising model in a cubic lattice [11] and De La Espriella and Buendía, on the magnetic behavior of a spins (3/2, 5/2) model, where they found that the ground state magnetizations of the system match with those obtained at T ¼0 in phase diagrams at finite temperature [12].…”
Section: Introductionmentioning
confidence: 65%
“…The phenomenon of ferrimagnetism has been one of the intensively studied subjects in condensed matter physics and statistical mechanics, because of their potential device applications in technologically important materials [2]. Moreover, the mixed spin (2, 5/2) Ising system is the prototypical system that has been used for studying the magnetic behaviors of molecular-based magnetic materials, such as AFe II Fe III (C 2 O 4 ) 3 [A = N(nÀCnH 2n+1 ) 4 , n = 3-5] [3][4][5][6][7][8][9][10][11][12]. Therefore, the purpose of this paper is to extend the work of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Los modelos de Ising mixtos juegan un papel importante en la simulación de dichas propiedades (Keskin y Polat, 2009;Behera et al, 2009). Se han realizado, por diversos métodos, diferentes estudios sobre estos modelos compuestos por dos o más subredes de espines mixtos (De La Espriella y Buendía, 2011;De La Espriella y Buendía, 2010;Deviren y Keskin, 2010;Yessoufou et al, 2009;Albayrak e Yigit, 2007;Buendía y Villarroel, 2007;Zhang et al, 2005;Htoutou et al, 2004;Zaim et al, 2009;Ekiz, 2008;Ekiz, 2005;Albayrak e Yigit, 2006).…”
Section: Introductionunclassified
“…Es importante establecer que estas propiedades son características del modelo, y no un resultado de la aproximación que se usa. Existen casos de algunos modelos, donde las aproximaciones de campo medio predicen la existencia de puntos de compensación, en los que simulaciones posteriores con métodos no perturbativos (Monte Carlo) han demostrado que no los poseen (Figueiredo et al, 2004;De La Espriella y Buendía, 2011).…”
Section: Introductionunclassified